Benthic foraminifera for the ecological status assessment of tourist marinas. (March 2023) - Franzo, A.; Caffau, M.; Nasi, F.; Marrocchino, E.; Paletta, M.G.; Bazzaro, M.; Cibic, T.
Highlights: Benthic foraminifera were investigated in three Mediterranean tourist marinas. Foraminifera responded to metal contamination ascribed to hull cleaning. Different indices were tested: FAI, d, H′, ES(100), Exp(H′bc), fAMBI. Marina's shape influences the accumulation of metals derived from careening activities. Exp(H′b, c) and fAMBI resulted the most informative tools for the monitoring of marinas. Abstract: Living benthic foraminifera were investigated in three tourist marinas of the Central Adriatic in order to test the suitability of these organisms for a quick and cost-effective assessment of the ecological quality status (EcoQS). Local high concentrations of biocidal metals (Cu, Zn, Cr, Sn, Ni and Pb) were measured in the sediments nearby the boathouse areas, i.e. where the careening activity takes place, suggesting that the accumulation of current and past antifouling residues is the main source of pollution in these particular maritime spaces. Factors such as the capacity of the marina, its shape as well as the location of the boathouse area concur to the degree of antifouling residues accumulation. Foraminifera responded to the different environmental conditions and to metal contamination in terms of abundance and species composition. At the boathouse stations these organisms were scarcely numerous and no living specimen was observed in the most polluted sediments. Three categories of indices were tested based on: (1) the percentages of abnormal tests, (2) biodiversity and (3) the sensitive-tolerant species occurrence (i.e. Foram-AMBI). The most diverse assemblage was observed at intermediate metal levels and seemed to be influenced by other environmental factors such as the presence of submerged vegetation that likely provides additional resources and increased heterogeneity. Unexpectedly, the station with the lowest metal levels was characterized by the least biodiverse assemblage. Notwithstanding, among the few species observed, at this site the dominant one was the sole species encountered in the present study that is recognized as sensitive, i.e. Ammonia parkinsoniana . Consequently, while the diversity indices provided very low values, Foram-AMBI outputs indicated the presence of an assemblage not exclusively dominated by opportunistic taxa. This result suggests a complementarity of these two categories of indices that should be taken into account for an accurate EcoQS assessment of tourist marinas.